2014
DOI: 10.2147/amep.s71759
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of integrated teaching in the improvement of an undergraduate ophthalmology curriculum

Abstract: PurposeConventional medical curriculum is the rule of medical teaching in Greek Medical Schools. Medical students are often taught irrelevant details with little or no reference to their potential clinical significance. Alternatively, integrated teaching warrants that the complete teaching material is covered by each faculty member not considering areas of personal expertise. The aim of this study was to evaluate the implementation of integrated teaching in ophthalmic training.MethodsThe main outcome measures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Li et al demonstrated that introducing additional ophthalmology lectures to third-year undergraduates greatly boosted their knowledge and influenced their motivation to teach [ 28 ]. Second, the contribution of the entire teaching team enables the integration of fundamental scientific knowledge and clinical practice for small student groups [ 29 ]. Thirdly, training techniques, such as didactic lectures, case presentations, and PowerPoint presentations, may have considerable benefits with variable efficacy outcomes [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Li et al demonstrated that introducing additional ophthalmology lectures to third-year undergraduates greatly boosted their knowledge and influenced their motivation to teach [ 28 ]. Second, the contribution of the entire teaching team enables the integration of fundamental scientific knowledge and clinical practice for small student groups [ 29 ]. Thirdly, training techniques, such as didactic lectures, case presentations, and PowerPoint presentations, may have considerable benefits with variable efficacy outcomes [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there are currently no publications in MedEdPORTAL detailing ophthalmic curricular content for medical students in their clinical years. Available evidenced-based ophthalmology curricula for preclinical and clinical medical students included use of integrated teaching, 11 team-based learning modules, 12 and intensive 1-and 2-day training courses. [13][14][15] While we did not find curricular content similar to our own on MedEdPORTAL, our literature search yielded one related article.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] Moreover, students do not achieve a comprehensive understanding and loose clinical relevance of the basic sciences at the time of their clinical training due to a significant diversity of interests, resources, and approaches between different departments while teaching different aspects of a particular topic. [ 3 ] Many innovations and trends in medical education have been undertaken globally in the past few years which include self-directed learning, problem-based learning, integrated teaching, and community orientation. [ 4 ]…”
Section: Introductionmentioning
confidence: 99%